Living longer by sitting less and moving more. (September 2015) - Stewart, Ralph A.H.; Benatar, Jocelyne; Maddison, Ralph
Abstract : Purpose of review: Regular exercise, physical fitness and sedentary behaviours are each known to be associated with cardiovascular and total mortality. This review evaluates recent research on these associations and its implications for guidelines on physical activity. Recent findings: In several large cohort studies, modest levels of exercise, much less than recommended in current guidelines, were associated with lower mortality. Avoiding prolonged sitting has also been associated with lower mortality risk. Most research suggests graded decreases in long-term mortality with an increase in usual physical activity and fitness. However, at very high exercise levels, these benefits may be attenuated, particularly in patients with known coronary heart disease. Summary: In sedentary persons, a modest increase in physical activity and avoiding prolonged sitting are likely to have important health benefits. Further research is needed to determine the most effective strategies for increasing physical activity.